Late clinical characteristics of infants with retinopathy of prematurity and treated with cryotherapy - Cerman, Eren (Int J Ophthalmol, 2016)
AIM: To describe the clinical characteristics and late results of patients with retinopathy of prematurity (ROP) treated with “6h cryotherapy”. METHODS: Out of 1252 infants screened for ROP, 52 patients were treated with temporal 6h cryotherapy from 1997 to 2005 were recalled to our clinic. Among these 23 patients were available and 46 eyes of 23 infants were included to evaluate for visual acuity, refractive error, ocular alignment, nystagmus, retinal examination (abnormal branching of retinal vessels, retinal thinning, latis degenerations, tortuosity of vessels, straightening of temporal vessels, narrowing of the angle of vessel in the juxtapapillary entrance, pigment changes, macular heterotopia), optic atrophy and optic disc cupping, axial length at birth and axial length at 1y. RESULTS: The median age at examination was 7 (5-18)y. In 32.6% of patients, the visual acuity was ≤20/200 and the mean best corrected visual acuity was 20/35 as measured with a Snellen chart. Mean spherical refractive error was -1.76±2.69 D. The degree of myopia at the last examination was found to be correlated with the elongation of the eye in the first year of life. Exotropia was present in 17.4% (n=8) of infants and esotropia in 13% (n=6). The most common retinal abnormality was abnormal branching of retinal vessels (82.6%) followed by retinal thinning (52.2%). CONCLUSION: The late clinical outcomes of infants with ROP treated in our clinic with cryotherapy seems to comparable with results of laser treatment.